Endogenous constitutions: Politics and politicians matter, economic outcomes don't - Bernd Hayo; Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
We study changes in the form of government as an example of endogenously determined constitutions. For a sample of 202 countries over the period 1950-2006, we find that most changes are relatively small and roughly equally likely to be either in the direction of more parliamentarian or more presidential systems. Based on a fixed effects ordered logit panel data model estimated over the period 1951-2000 for 146 countries, we find that such changes in the constitution can be explained by characteristics of the political system, internal and external political conflicts, and political leaders, whereas economic and socio-demographic variables do not matter.
Keywords: H11; K10; P48; 330; constitutional change; form of government; endogenous constitutions; separation of powers; relevance of leaders; Verfassungsreform; Politisches System; Gewaltenteilung; Politiker; Schätzung; Welt